Transcriptomic, proteomic, and metabolomic analyses identify candidate pathways linking maternal cadmium exposure to altered neurodevelopment and behavior - Kathleen M. Hudson (Nature Portfolio, 2021)
Abstract Cadmium (Cd) is a ubiquitous toxic heavy metal of major public concern. Despite inefficient placental transfer, maternal Cd exposure impairs fetal growth and development. Increasing evidence from animal models and humans suggests maternal Cd exposure negatively impacts neurodevelopment; however, the underlying molecular mechanisms are unclear. To address this, we utilized multiple -omics approaches in a mouse model of maternal Cd exposure to identify pathways altered in the developing brain. Offspring maternally exposed to Cd presented with enlarged brains proportional to body weights at birth and altered behavior at adulthood. RNA-seq in newborn brains identified exposure-associated increases in Hox gene and myelin marker expression and suggested perturbed retinoic acid (RA) signaling. Proteomic analysis showed altered levels of proteins involved in cellular energy pathways, hypoxic response, and RA signaling. Consistent with transcriptomic and proteomic analyses, we identified increased levels of retinoids in maternally-exposed newborn brains. Metabolomic analyses identified metabolites with significantly altered abundance, supportive of changes to cellular energy pathways and hypoxia. Finally, maternal Cd exposure reduced mitochondrial DNA levels in newborn brains. The identification of multiple pathways perturbed in the developing brain provides a basis for future studies determining the mechanistic links between maternal Cd exposure and altered neurodevelopment and behavior.